A green route for biodiesel production from waste cooking oil over base heterogeneous catalyst. (17th June 2019) - Farooq, Muhammad; Ramli, Anita; Naeem, Abdul; Noman, Muhammad; Shah, Liaqat Ali; Khattak, Noor Saeed; Perveen, Fouzia
Summary: The present work describes the synthesis of porous BaSnO3 by eco‐friendly sol‐gel method using albumin as a bio‐template agent, and its application as a solid base catalyst in biodiesel production from waste cooking oil. The physico‐chemical, textural, and morphological properties of the catalyst were evaluated by X‐ray diffraction (XRD), Brunauer‐Emmett‐Teller (BET), field emission scanning electron microscopy (FESEM), and temperature programmed desorption (TPD)–CO2 techniques. The synthesized catalyst showed considerable stability, efficient catalytic activity, and negligible metal leaching. The satisfactory performance of the catalyst could be ascribed to the presence of basic sites of different strength on the surface of the catalyst. The catalyst produced maximum biodiesel yield of 96% at optimum reaction conditions of 90°C reaction temperature, methanol to oil molar ratio of 10:1, catalyst dosage of 6 wt%, and reaction time of 2 hours. Moreover, the catalyst showed substantial reusability up to five reaction cycles without any considerable decrease in transesterification activity. Abstract : This work aims to use BaSnO3 as an efficient solid base catalyst for biodiesel production from waste cooking oil under suitable reaction conditions. Moreover, the synthesized catalyst showed good stability and could be used five times for biodiesel production.